HybridConcatenated Coding Scheme for MIMO Systems - Ilesanmi Banjo Oluwafemi (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Abstract: Inthis paper, two hybrid concatenated super-orthogonal space-time trellis codes(SOSTTC) applying iterative decoding are proposed for flat fading channels. Theencoding operation is based on the concatenation of convolutional codes,interleaving and super-orthogonal space-time trellis codes. The firstconcatenated scheme consists of a serial concatenation of a parallelconcatenated convolutional code with a SOSTTC while the second consists ofparallel concatenation of two serially concatenated convolutional and SOSTTCcodes. The decoding of these two schemes is described, their pairwise errorprobabilities are derived and the frame error rate (FER) performances areevaluated by computer simulation in Rayleigh fading channels. The proposedtopologies are shown to perform better than existing concatenated schemes with aconstituent code of convolutional andspace-time codes in literature.